Comparison of Postoperative Analgesic Effects of Medetomidine-Ketamine, Isoflurane and Medetomidine-Butorphanol, Isoflurane Combinations in Anesthesia for Ovariohysterectomy in Cats - Yalım UZEL; Muharrem EROL (ISPEC Journal of Agricultural Sciences)
Mild to moderate pain occurs after spaying in cats. Pain is a condition that must be treated. Analgesics can be used alone or in combination to achieve more effective results. The aim of this study is to compare the postoperative analgesic effects of combinations of medetomidine, ketamine, isoflurane, meloxicam and medetomidine, butorphanol, isoflurane, meloxicam in cats undergoing ovariohysterectomy surgery. The study material consisted of healthy female cats (n=20) of various breeds and at least 6 months of age. All cats received pre-anesthetic medetomidine at a dose of 80 μg kg-1 intramuscularly, with the first group receiving ketamine 0.5 mg kg-1 subcutaneously as an analgesic, and the second group receiving 0.4 mg kg-1 subcutaneously of butorphanol. Anesthesia induction (5%) and maintenance (2%) were provided by inhalation anesthesia (isoflurane). The incision was made in the middle third of the area, divided into three parts between the navel and the pubis. To measure the differences in pain between the groups formed after the operation, the heart rate, respiratory rate, and body temperature of the cats were measured at postoperative 0, 1, 2, 3, 4, 6, and 12 hours, and their body language was evaluated according to the 'Colorado State University Feline Acute Pain Scale'. Pain scores were found to be higher in the butorphanol group than in the ketamine group at postoperative hours one and two. While heart rate and body temperature values between the groups were similar, respiratory rates differed among the groups. These findings suggest that subanesthetic/analgesic doses of ketamine are more potent in postoperative pain management of infertility compared to analgesic doses of butorphanol.